Manajemen Risiko Banjir Pada Masyarakat Rentan - Fadhil, Satria Nauval; Rachmawati, Farida; Rahman, Moh. Arif (Jurnal Aplikasi Teknik Sipil, 2024)
Floods can have a worse impact on vulnerable communities compared to the general population. Surabaya City still frequently experiences floods with an average inundation height of 10,92 cm and duration of 19,12 minutes. Vulnerable communities are those with high risks, such as the elderly, pregnant women, people with disabilities, and the poor. Based on this issue, this research aims to analyze the level of disaster risk that connects hazards, vulnerability, and capacity of vulnerable communities. The study focuses on four neighborhoods with the most severe flooding based on Surabaya City inundation data. The research is divided into two stages: the first stage determines the weight of indicators for each variable using pairwise comparison, and the second stage involves surveying 120 respondents from vulnerable communities to assess scores for hazard, vulnerability, and capacity variables, which are then used to calculate the risk level. The research results indicate that the highest risk level occurs in Gundih and Dukuh Pakis neighborhoods with a score of 3,52. This is due to the high vulnerability caused by drainage channel conditions and building elevations below road level, posing a threat to vulnerable communities.